Penderitaan Ayub dan Kekerasan Massa: Refleksi René Girard dan Hannah Arendt - Iman Sukmana (Respons: Jurnal Etika Sosial, 2009)
Abstract: Assuming that violence can be found in many fields in our life, this article proposes the logic of violence in the story of Job. It shows us how Job suffers in his life. His suffering was absurd in his eyes. He didn’t understand why he should suffer. The problem was not only why he got suffering in his life, but also why his friends and people around him changed their attitudes towards him. Many people thought that Job suffered because of his sin. Their thought was mimetic among them. So, many people had the same perception about Job. There was an unanimity of opinion which judged that Job was a sinner. They asked Job to confesse his sin if he wanted to be saved. The unanimity of their voice became verbal abuse to Job, but people didn’t know that they made Job as a “scapegoat”.Kata Kunci: Ayub, kekerasan, kambing hitam, mimesis, banal, massa.